A proposta de uma estética a partir de Spinoza e sua vinculação com a ética - Fachinelli, Lucas Sartor (My University, 2024)
This thesis explores the possibility and nature of an aesthetics grounded in Spinoza's philosophical system. It questions how the aesthetic discipline, developed from the Spinozist system, can establish an argumentative paradigm in the context of the third kind of knowledge. The study starts from the premise that, despite the apparent limitations imposed by the Spinozist system on the conception of aesthetics, an investigation into the ontological organization of the system reveals a possibility of aesthetic understanding that aligns with and complements Spinozist ethics. Therefore, the main objective of this thesis is to examine the argumentative openings of Spinoza's system that allow for the development of aesthetics as an argumentative structure to achieve the third kind of knowledge. The research proposes that beauty, in Spinoza, is not merely a subjective or relative concept; aesthetics, when assessed from the ontological levels of substance and the progression of kinds of knowledge, enables the identification of a singular beauty property in objects, which, in turn, produces an affection called beautiful. This property, by its ontological presence, is capable of generating in humans who come into contact with it a process of activity that can lead to higher levels of understanding of God, establishing aesthetics as a complement to Spinoza's system, which aims at human freedom and beatitude. To substantiate this process, this thesis develops an exposition of Spinoza's ontological system and, from its methodological organization, investigates four complementary possibilities for grounding aesthetics through the concepts of affection, activity, love, and imagination as a symbolic apprehension of beauty. Through these concepts, an aesthetics is systematized from Spinoza's philosophy, and from it, considerations on art and creativity are made. The thesis concludes by demonstrating how aesthetics relates to ethics and complements Spinoza's system, serving as a viable alternative in the development of freedom both personally and in a social context. [resumo fornecido pelo autor]
Esta tese explora a possibilidade e a natureza de uma estética fundamentada no sistema filosófico de Spinoza. Questiona-se como a disciplina estética, desenvolvida a partir do sistema spinozista, pode estabelecer um paradigma argumentativo no contexto do terceiro gênero de conhecimento. O estudo parte da premissa de que, apesar das aparentes limitações impostas pelo sistema spinozista à concepção de estética, uma investigação sobre a organização ontológica do sistema revela uma possibilidade de compreensão estética que se alinha e complementa a ética spinozista. Por isso, o objetivo principal desta tese é examinar as aberturas argumentativas do sistema de Spinoza que possibilitam o desenvolvimento da estética como uma estrutura argumentativa para se alcançar o terceiro gênero de conhecimento. A pesquisa propõe que o belo, em Spinoza, não é um conceito meramente subjetivo ou relativo; a estética, se avaliada a partir dos níveis ontológicos da substância e a progressão dos gêneros de conhecimento, possibilita a identificação de uma propriedade singularmente bela em objetos, que, por sua vez, produz uma afecção denominada de beleza. Esta propriedade, por sua presença ontológica, é capaz de gerar nos humanos que entram em contato com ela um processo de atividade que pode levar aos níveis mais elevados do entendimento de Deus, estabelecendo a estética como um complemento ao sistema de Spinoza, que visa a liberdade e beatitude humana. Para fundamentar esse processo, esta tese desenvolve uma exposição do sistema ontológico de Spinoza e, a partir de sua organização metodológica, investiga quatro possibilidades complementares de fundamentação da estética pelos conceitos de afecção, atividade, amor e a imaginação como apreensão simbólica do belo. Através desses conceitos, é sistematizada uma estética a partir da filosofia de Spinoza, e por ela são realizadas considerações sobre a arte e a criatividade. A tese conclui demonstrando como a estética se relaciona com a ética e complementa o sistema de Spinoza, servindo como uma alternativa viável no desenvolvimento da liberdade tanto pessoal quanto em um âmbito social. [resumo fornecido pelo autor]
Keywords: Spinoza, Benedictus de, 1632-1677; Estética; Ética; Aesthetics; Ethics